2018
DOI: 10.1161/strokeaha.118.021137
|View full text |Cite
|
Sign up to set email alerts
|

Perivascular Spaces Volume in Sporadic and Hereditary (Dutch-Type) Cerebral Amyloid Angiopathy

Abstract: Background and Purpose- Magnetic resonance imaging visible perivascular spaces in the centrum semiovale (CSO-PVS) have been associated with cerebral amyloid angiopathy (CAA).We aimed to further confirm this link by evaluating CSO-PVS volume in pathologically-demonstrated sporadic and genetically-demonstrated hereditary forms of the disease. Methods- We studied a retrospective hospital-based cohort consisting of 63 individuals aged >55 having brain magnetic resonance imaging and pathological assessment of CAA (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 39 publications
(47 reference statements)
2
26
0
Order By: Relevance
“…For example, cortical superficial siderosis indicates perivascular iron accumulation in pial arteries and arterioles reflecting cerebral microbleeds [12,14,23]. Another noted perivascular change associated with CAA is the presence of dilated perivascular spaces, particularly around penetrating arterioles with amyloid deposition [8,24]. Although the cause of this perivascular alteration remains unclear this space contains CSF and interstitial fluid (ISF) that under normal conditions plays an important role in Aβ clearance from brain [25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, cortical superficial siderosis indicates perivascular iron accumulation in pial arteries and arterioles reflecting cerebral microbleeds [12,14,23]. Another noted perivascular change associated with CAA is the presence of dilated perivascular spaces, particularly around penetrating arterioles with amyloid deposition [8,24]. Although the cause of this perivascular alteration remains unclear this space contains CSF and interstitial fluid (ISF) that under normal conditions plays an important role in Aβ clearance from brain [25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…However, independent of AD, clinically CAA is a significant contributor to vascular-mediated cognitive impairment and dementia (VCID) [3,4,7]. As a prominent small vessel disease CAA contributes to the cognitive decline in VCID in several ways by promoting perivascular neuroinflammation, impaired cerebral blood flow and ischemic infarcts, cerebral microbleeds, and larger hemorrhages, all of which can result in neuronal dysfunction, neuronal loss and white matter damage [3,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Cerebral amyloid angiopathy shares Aβ pathology with AD, and an experimental study has demonstrated that CSF inflow and ISF clearance in the brain are suppressed in a mouse model of AD and in these the ISF/CSF dynamics is suppressed prior to the significant accumulation of Aβ [ 74 ]. One observational study on humans reported that the dilatation of perivascular space in the centrum semiovale, which may suggest impaired ISF drainage, significantly correlated with the existence of cerebral amyloid angiopathy even in the absence of any lobar hemorrhages [ 75 ].…”
Section: Disorders Categorized In Cns Interstitial Fluidopathiesmentioning
confidence: 99%
“…Slice thickness was 5 mm with 1.5 mm gap between slices. Parameters for 1.5T scanner, T1WI sequence: repetition time (TR), 1,990 ms; echo time (TE), 8 2 . MRI markers of CSVD, including BG-EPVS, WMH, and lacunes were assessed blinded to clinical information by a trained neuroradiologist (JW), according to previous literature (19,20).…”
Section: Mr Imagingmentioning
confidence: 99%
“…Perivascular spaces (PVS) refer to tiny fluid-filled cavities surrounding the cerebral small perforating blood vessels that penetrate the brain parenchyma (1). PVS are normally invisible on conventional magnetic resonance image (MRI) and become visible on neuroimaging when PVS are presumably prominent or dilated (2). Basal ganglia (BG) is a common site for enlarged perivascular spaces (EPVS) formation where the largest cerebrospinal fluid (CSF) influxes occur along large ventral perforating arteries (3,4).…”
Section: Introductionmentioning
confidence: 99%